The concept of Yin and Yang in Bright Sheng’s “My Other Song” - Qian, Deng; Loo, Fung Chiat (Human Resource Management Academic Research Society, 2022)
This paper explores the ancient Chinese concepts involved in Bright Sheng's solo piano work “My Other Song,” as well as the compositional developments between “My Other Song” and “My Song” composed 17 years apart, drawing on the composer's answer, “I feel 100% Chinese and 100% American,” he gave in an interview in the Wall Street Journal. The Chinese culture of I Ching is over a thousand years long, and its derivative theory of yin and yang has been used by contemporary Chinese composers to innovate approach to contemporary composition. This paper provided an in-depth analysis of Sheng’s work in terms of pitch structure, tonality, dynamics, motifs, and musical gestures from the perspective of ancient Chinese and Confucian thought, the main concepts of I Ching, Yin and Yang theory. The paper concludes by considering the process and methods of integrating philosophical ideas into musical compositions, as well as the effects in modern music.